The business of banking : papers and group discussions from the 26th International Banking Summer School held at Christ Church, Oxford, July 1973 - Institute of Bankers (Great Britain) (London : Institute of Bankers, 1973)
This book contains the eight keynote papers given at the International Banking Summer School (I.B.S.S.), together with the additional study documents used for syndicate discussions by the bankers from over 50 countries who were selected to attend.
Includes bibliographical references p. 237-241
hza 27/11/2018
Loans
Keywords: Banks and banking